Head-discharge relationships for rectangular flat-crested slit weir / Rosley Jaafar - Jaafar, Rosley (Universiti Teknologi MARA, Perlis, 2015)
The rectangular weir is the most commonly used device in channel and laboratory for flow measurement due to its simplicity. The rectangular sharp-crested slit weir has been shown to be good at measuring small (< 0.005 m3/s) flow rates. In this study, the rectangular slit weir concept is extended to find the head-discharge relationship of water flows over a contracted rectangular flat-crested slit weir under free flow conditions. The head-discharge relationship is determined experimentally using a nine different weir heights with 10 mm weir width and 4 mm weir crest thickness at small discharges (< 0.00067 m3/s). The experimental data of actual and predicted discharge is verified by using a statistical analysis. A linear regression equation correlating the head-discharge relationship provides an accurate prediction of free flow discharge over the weir to yield results within 2.1% error of actual discharges and have a strong relationship. The presented head-discharge equation can use to estimate the discharge flow of water over rectangular flat-crested slit weir with an appropriate limitation.